VISUAL BASIC APPLICATION DATA MANAGEMENT SERVICES FOR PATIENTS IN CLINIC REGISTRATION AL FALAH - Ahmad Rojafi; Diyah Ruri Irawati, SKom, MMSI Diyah Ruri Irawati, SKom, MMSI (Jurnal Sistem Informasi, 2006)
This application program is designed to simplify the administration of the clinic ofAl-Falah, because by using this application program activities and long termenrollment of new patients will be rapidly carried out. Especially for older patientswho forgot to bring the card to treatment, patients can be served faster because of theprogram to search for patient data is easily and quickly, the data can be easy onlooking good with numbers and patient medical records with patient names. Printingreports record medic available if necessary by a physician, physician data report, andreport patient data per day.